Investigating mechanical deformation's role in cochlear implant durability. - Tatiana Blank; André Marcel Ahrens; Christian Klose; Demircan Canadinç; Thomas Lenarz; Hans Jürgen Maier (PLoS ONE, 2024)
Platinum and platinum-based alloys are used as the electrode material in cochlear implants because of the biocompatibility and the favorable electrochemical properties. Still, these implants can fail over time. The present study was conducted to shed light on the effects of microstructure on the electrochemical degradation of platinum. After three days of stimulation with a square wave signal, corrosive attack appeared on the platinum surface. The influence of mechanical deformation, in particular rolling, on the corrosion resistance of platinum was also prominent. The cyclic voltammetry showed a clear dependence on the electrolyte used, which was interpreted as an influence of the buffer in the artificial perilymph used. In addition, the polarization curves showed a shift with grain size that was not expected. This could be attributed to the defects present on the surface. These findings are crucial for the manufacture of cochlear implants to ensure their long-term functionality.